TRADEMARKS IN SUSTAINABLE FASHION: A Comparative Legal Analysis of Indonesia and Italy - Situmeang, Ampuan; Alhakim, Abdurrakhman; Fitri, Winda; Trinh, Hien (Fakultas Syariah, 2023)
Trademarks have played a significant role in safeguarding intellectual property within the fashion industry and have been instrumental in upholding the reputation of various companies, particularly those aspiring to adopt sustainability concepts. This research aims to delineate the legal challenges and potential solutions for protecting intellectual property rights related to trademarks and the integrity of claims for sustainability implementation in Indonesia, employing normative research methods and comparative analysis with Italy's legal framework. The analysis reveals several structural differences between Indonesia and Italy's trademark legal frameworks despite sharing similar objectives. Italy has already been able to foster the integrity of sustainable claims in the fashion industry through regulations from the European Union although no direct connection to trademarks exists. On the other hand, Indonesia has yet to regulate the integrity of sustainable claims in the fashion industry although it possesses a sufficient foundational framework that could be further developed through its connection to the communal intellectual property protection system. Secara tradisional, merek memiliki peran penting dalam melindungi kekayaan intelektual di dalam industri fesyen dan telah menjadi kunci dalam menjaga reputasi berbagai perusahaan, terutama yang berkeinginan menerapkan konsep keberlanjutan. Penelitian ini bertujuan untuk menguraikan tantangan hukum dan solusi potensial dalam melindungi hak kekayaan intelektual yang terkait dengan merek serta menjaga integritas klaim implementasi keberlanjutan di Indonesia, dengan menggunakan metode penelitian normatif dan analisis perbandingan dengan kerangka hukum Italia. Analisis ini mengungkapkan beberapa perbedaan struktural antara kerangka hukum merek di Indonesia dan Italia, meskipun memiliki tujuan yang serupa. Italia telah berhasil menggalang integritas klaim keberlanjutan di industri fesyen melalui regulasi dari Uni Eropa, meskipun tidak ada keterkaitan langsung dengan merek. Di sisi lain, Indonesia masih harus mengatur integritas klaim keberlanjutan di industri fesyen, meskipun memiliki landasan kerangka kerja yang memadai yang bisa lebih dikembangkan melalui keterhubungannya dengan sistem perlindungan kekayaan intelektual komunal.